The Impact of Leisure Time Allocation on Human Capital Accumulation in High School Students: A Study on Health and Academic Performance - Zhang, Qiyue (International Journal of Global Economics and Management, 2024)
Human capital is a critical resource for economic development, and its accumulation depends not only on academic performance but also on physical and mental health. Therefore, understanding how leisure time allocation influences human capital accumulation is essential. This study, based on a survey of 51 high school students, examines the effects of online and offline leisure activities on their health and academic performance. The results indicate that excessive online leisure time is associated with lower physical activity levels, higher BMI, and increased risk of myopia, all of which have significant negative impacts. Although the sample size is relatively small and there is little variation in academic performance, some students may have overestimated their academic achievements in the questionnaire, making it difficult to clearly reflect the effect of leisure time on academic outcomes. Overall, a balanced allocation of leisure time, integrating both online and offline activities, contributes to better physical and mental health, thus promoting comprehensive human capital development. The study suggests that schools encourage students to balance their leisure time, make reasonable use of the internet, and engage in physical activities to improve both health and academic outcomes.